The non-homologous end-joining pathway is involved in stable transformation in rice - Saika, Hiroaki; Nishizawa-Yokoi, Ayako; Toki, Seiichi (Frontiers in Plant Science, 2014)
Stable transformation with T-DNA needs the coordinated activities of many proteins derived from both host plant cells and Agrobacterium. In dicot plants, including Arabidopsis, it has been suggested that non-homologous end-joining (NHEJ)—one of the main DNA double-strand break repair pathways—is involved in the T-DNA integration step that is crucial to stable transformation. However, how this pathway is involved remains unclear as results with NHEJ mutants in Arabidopsis have given inconsistent results. Recently, a system for visualization of stable expression of genes located on T-DNA has been established in rice callus. Stable expression was shown to be reduced significantly in NHEJ knock-down rice calli, suggesting strongly that NHEJ is involved in Agrobacterium-mediated stable transformation in rice. Since rice transformation is now efficient and reproducible, rice is a good model plant in which to elucidate the molecular mechanisms of T-DNA integration.